Sonication method synergism with rare earth based nanocatalyst： preparation of NiFe2-xEuxO4 nanostructures and its catalytic applications for the synthesis of benzimidazoles, benzoxazoles, and benzothiazoles under ultrasonic irradiation - Ziarati, Abolfazl; Sobhani-Nasab, Ali; Rahimi-Nasrabadi, Mehdi; Ganjali, Mohammad Reza; Badiei, Alireza (Journal of rare earths, 2017)
A simple and practical ultrasonically synthetic strategy for the preparation of rare-earth based catalyst, nanostructured NiFe2-xEuxO4 was developed. The structtre of NiFe2-xEuxO4 was characterized by various analyses such as X-ray diffraction （XRD）, scanning electron microscopy （SEM） and fourier transform infrared spectroscopy （FT-IR）. The catalytic performance of NiFe2-xEuxO4 was evaluated for the synthesis of benzimidazoles, benzoxazoles and benzothiazoles under ultrasonic irradiation. All reactions were completed in short times and all products were obtained in good to excellent yields in presence of the rare-earth based catalyst. Besides, NiFe2-xEuxO4 could be recovered for 6 times without noticeably decreasing the catalytic activity.